EFFICACY OF ONDANSETRON ALONE AND ONDANSETRON PLUS DEXAMETHASONE IN PREVENTING NAUSEA AND VOMITING AFTER MIDDLE EAR SURGERY - Wadood, Fazal; Muhammad, Raza; Jamil, Mohammad; Nisa, Waqar un (Journal of Ayub Medical College Abbottabad, 2014)
Background: Post-operative nausea and vomiting is one of the most frequently occurring side effects affecting one third of the cases. Objective of the study was to compare the efficacy of ondansetron alone and ondansetron plus dexamethasone in preventing postoperative nausea and vomiting after middle ear surgery. Methods: This randomized controlled trial was conducted at the Anaesthesia and ENT departments of Ayub Medical College, Abbottabad from January-June 2012. Forty American Society of Anaesthesiologists (ASA) I and 2 physical status patients undergoing middle ear surgery were divided into two groups by blocked randomization. Patients in group-1 (n=20) received ondansetron 4 mg while group-II (n=20) received ondansetron 4 mg with dexamethasone 8 mg just before start of operation. The whole postoperative period of 24 hours was divided into two phases, early 0-6 hours and late phase 6-24 hour. Results: Nausea score and its frequency was significantly higher in Group-I (p<0.05). Vomiting and its frequency were found more in group-I patients. In Group-II, the nausea score was significantly less (p<0.01) at 6 and 24 hours after surgery. The total incidence of vomiting was reduced from 28% in group-1 to 6% in group-II. Rescue antiemetic requirement was significantly less (p<0.01) in group-II. Conclusion: Prophylaxis with a combination of ondansetron and dexamethasone decreased the incidence of nausea and vomiting after middle ear surgery. Keywords: Nausea and vomiting, Middle ear surgery, Dexamethasone, Ondansetron